PENGARUH PARTISIPASI ANGGARAN, TEKNOLOGI INFORMASI, DAN KUALITAS INFORMASI MANAJEMEN TERHADAP KINERJA MANAJERIAL (Studi Empiris Pada Perusahaan Manufaktur Di Kabupaten Pati) - Ayu Nuari Dita Pratikyo; Sri Suprapti (FEB UNTAG Semarang, 2016)
This study aims to analyze problems that occur in companies manufacturing in Pati regency about the effect of budget participation, information technology, and the quality of management information on managerial performance, in which the three variables are closely related to increase profits for the company. Data used by researchers primary data obtained from the questionnaire. The number of respondents used in this study were 190 respondents consisting of five managers (HR manager, Production, Operations, Finance, Marketing) in each company. The analytical tool used in this study using multiple regression.The results showed a positive and significant relationship between budget participation on managerial performance of 0.529. As for the second hypothesis, the test results showed a positive and significant relationship between information technology to managerial performance of 0.331. Hypotheses for the latter show a positive and significant relationship between the quality of management information on managerial performance amounted to 0,439.Keyword : Parcitipative budgeting, Information Technology, Quality Of Management Information, Managerial Performance